President Trump's First Term The Year in C-SPAN Archives Research, Volume 5 - Browning, Robert X. (Purdue University Press, 2020)
C-SPAN is the network of record for US political affairs, broadcasting live gavel-to-gavel proceedings of the House of Representatives and the Senate, and to other forums where public policy is discussed, debated, and decided--without editing, commentary, or analysis and with a balanced presentation of points of view. The C-SPAN Archives, located adjacent to Purdue University, is the home of the online C-SPAN Video Library. The Archives has recorded all of C-SPAN's television content since 1987. Extensive indexing, captioning, and other enhanced online features provide researchers, policy analysts, students, teachers, and public officials with an unparalleled chronological and internally cross-referenced record for deeper study. Books in this series present the finest interdisciplinary research utilizing tools of the C-SPAN Video Library. Each volume highlights recent scholarship and comprises leading experts and emerging voices in political science, journalism, psychology, computer science, communication, and a variety of other disciplines. Each section within each volume includes responses from expert discussants. Developed in partnership with the Center for C-SPAN Scholarship & Engagement in the Purdue University Brian Lamb School of Communication with support from the C-SPAN Education Foundation, this volume is guided by the ideal that research based on C-SPAN video can increase our understanding of American politics and democracy based on the ideals of our American experiment. The fifth volume of the C-SPAN Archives research focuses primarily on the Trump presidency in the first term. Chapters address his moral language, his rhetoric on climate change, and African American support for Trump. Other chapters use the C-SPAN Archives to study congressional influence on immigration policy, nonverbal cues in congressional speeches, and local and national perspectives on congressional debates.